Comparison of balanced crystalloids versus normal saline in patients with diabetic ketoacidosis: a meta-analysis of randomized controlled trials - Liu, Yuting; Zhang, Jianfeng; Xu, Xiaoya; Zou, Xiaoyun (Frontiers in Endocrinology, 2024)
Purpose: The optimal resuscitative fluid for patients with diabetic ketoacidosis (DKA) remains controversial. Therefore, our objective was to assess the effect of balanced crystalloids in contrast to normal saline on clinical outcomes among patients with DKA. Methods: We searched electronic databases for randomized controlled trials comparing balanced crystalloids versus normal saline in patients with DKA, the search period was from inception through October 20th, 2023. The outcomes were the time to resolution of DKA, major adverse kidney events, post-resuscitation chloride, and incidence of hypokalemia. Results: Our meta-analysis encompassed 11 trials, incorporating a total of 753 patients with DKA. There was no significant difference between balanced crystalloids and normal saline group for the time to resolution of DKA (MD -1.49, 95%CI -4.29 to 1.31, P=0.30, I2=65%), major adverse kidney events (RR 0.88, 95%CI 0.58 to 1.34, P=0.56, I2=0%), and incidence of hypokalemia (RR 0.80, 95%CI 0.43 to 1.46, P=0.46, I2=56%). However, there was a significant reduction in the post-resuscitation chloride (MD -3.16, 95%CI -5.82 to -0.49, P=0.02, I2=73%) among patients received balanced crystalloids. Conclusions: Among patients with DKA, the use of balanced crystalloids as compared to normal saline has no effect on the time to resolution of DKA, major adverse kidney events, and incidence of hypokalemia. However, the use of balanced crystalloids could reduce the post-resuscitation chloride. Systematic Review Registration: https://osf.io/c8f3d